Pengaruh Kepemimpinan Kepala Madrasah dan Kinerja Guru terhadap Prestasi Belajar Siswa Madrasah Ibtidaiyah - Sulis Rokhmawanto; Muna Fauziah; Zahroh Zahroh (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2022)
This research is intended to answer the following problems: 1) Is there any influence of the leadership of the madrasa head on student achievement? 2) Is there an effect of teacher performance on student achievement? 3) Is there an influence of the leadership of the madrasa head and teacher performance together on student achievement at Madrasah Ibtidaiyah Ma'arif NU 1 Kalijaran? This type of research is a quantitative research. The data was obtained by using questionnaires, observations, interviews and documentation. All data obtained were then analyzed using quantitative data analysis. The results of the study found that: 1) The leadership of the madrasah head had a positive and significant effect on student achievement as evidenced by the regression calculation obtained a positive constant of 3,017 where the variable of Madrasah Principal Leadership (X1) had a significant number > 0.05, which was 0.915 with a calculated t value 1.108. The more the leadership of the madrasa head increases, the learning achievement of students will increase; 2) Teacher performance has a positive and significant effect on student achievement with the Teacher Performance variable (X2) having a significant number > 0.05, which is equal to 0.17 with a t-value of 2,505, it is concluded that the Teacher Performance variable has a positive and significant effect on learning achievement; 3) The leadership of the madrasah head and teacher performance simultaneously influence the results of student achievement at Madrasah Ibtidaiyah Ma'arif NU 1 Kalijaran which is obtained from the calculation of F count of 159.686 with a significance of <0.05, which is equal to 0.000. From these results it is known that the regression line equation can be used to predict Learning Achievement, or it can be said that the Madrasah Principal Leadership and Teacher Performance variables jointly affect Learning Achievement.